Kinetic Study of Laboratory Scale Composting Process - Ng, Hon Seng (1999)
Solid waste generated in Malaysia constitutes of large portion of organic material that can be readily composted. Compo sting which dispose off the organic material, and at the same time producing usable compost as the end product is thought to be a good option for organic wastes disposal. This project accomplished kinetic study of compo sting process that may be of use for the design and process optimization. This study was conducted under controlled laboratory experimental set up; operated at 40°C, equipped with aeration facility, with boiled rice and soil as the organic material. The volatile solid was employed as the process indicator throughout the course of this project. The data was manipulated and best fitted based on the procedure of Michaelis Menten model. The model resulted in an experimental exponential equation. It also enable the formulation of another linear equation therefrom, that eventually give in the value ofKl and K2 (whereby Kl is the process constant and K2 is the process variable of a compo sting system). The model produced has a mathematical expression of y = 88.357x-O· 2490 with R-square value of 0.8148, and gave in the value of Kl and K2 of 80.6102 and 1.0502. The model was verified by another set of verification data. Three verification methods were carried out, that were Differences analysis, Percent of error analysis, and Ratio of experimental data over verification data. The results showed that the model is capable of describing the actual status of the process. However, if this model is to be applied for the design of composting facility, Monod equation that governs the microbial aspect should be incorporated.